1986
DOI: 10.1098/rspb.1986.0034
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory head roll in the blowflyCalliphoraduring flight

Abstract: Video records were made of the blowfly Calliphora erythrocephala L. mainly during tethered flight in a wind-tunnel, to study its movements about the longitudinal body axis (roll). During undisturbed flight, flies hold their head on average aligned with the body but may turn it about all three body axes. Pitch and yaw turns of the head are comparatively small (20°), whereas roll turns can be large (90°), and fast (1200° s -1 ). When passively rolled, flies produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(46 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…The dorsal light response and gravity reception are potential mechanisms. In tethered flies, Hengstenberg et al (1986) found a very similar head roll response to a continuously rotating drum, with the difference that flies turned their head by +908, which is close to the mechanical limits of the fly's neck joint. In these experiments, however, the authors eliminated gravity and light gradients as an orienting vector for roll movements by mounting the fly vertically in a homogeneously illuminated striped drum.…”
Section: Discussionmentioning
confidence: 83%
“…The dorsal light response and gravity reception are potential mechanisms. In tethered flies, Hengstenberg et al (1986) found a very similar head roll response to a continuously rotating drum, with the difference that flies turned their head by +908, which is close to the mechanical limits of the fly's neck joint. In these experiments, however, the authors eliminated gravity and light gradients as an orienting vector for roll movements by mounting the fly vertically in a homogeneously illuminated striped drum.…”
Section: Discussionmentioning
confidence: 83%
“…Although the haltere is subjected to inertial and gravitational forces, the sensory cells appear most sensitive to Coriolis forces acting on the end-knob during angular rotation of the body (Nalbach, 1993(Nalbach, , 1994. The compensatory reactions elicited by the halteres include head movements and changes in the wingstroke kinematics (Hengstenberg et al, 1986;Hengstenberg, 1988). The control of the wingstroke resides with a set of 17 small steering muscles that are typically active only during steering maneuvers .…”
Section: Abstract: Haltere; Gap Junctions; Sensory Motor Reflex; Flimentioning
confidence: 99%
“…extrafoveal), they are seen less well than when correctly centered; familiar objects are less well recognized when seen in an unfamiliar orientation. [1][2][3] Thus, best visual perception requires upright stabilization of the eyes whereas high manoeuverability, as in a flying animal may require fast movements and oblique postures. This conflict of interest can be partly solved by mobile eyes which may be stabilized temporarily an the visual scene 5,6 and crustacea 7,8 but, until recently, very little in insects.…”
mentioning
confidence: 99%